Q: 3x2 plus 3x minus 60

Write your answer...

Submit

Related questions

3x2 + 27x +60

3x^2+3x-60=3(x^2+x+20)=3(x+5)(x-4)

i like men

3x2 - 3x - 60 = 3(x2 - x - 20) = 3(x2 - 5x + 4x - 20) = 3(x[x - 5] + 4[x - 5]) = 3(x + 4)(x - 5)

no 3x2=6 then 4x-15= -60 so 6 added with - 60 = -54

-3x2 = 5 + 3x (add 3x2 to both sides)0 = 3x2 + 5 + 3x or3x2 + 3x + 5 = 0 (since the discriminant is less than zero, we have complex roots)x = [-3 ± √[(32 - 4(3)(5)]]/2(3)x = [-3 ± √(9 - 60)]/6x = (-3 ± √-51)/6x = (-3 ± i√51)/6x = (-3 + i√51)/6 = -1/2 + (√51/6)i orx = (-3 - i√51)/6 = -1/2 - (√51/6)i

60 plus 9 plus 100 minus 100 equals 69,see 60 + 9 = 69, 69 + 100 = 169 - 100 = 69 and that is the awnser to 60 plus 9 plus 100 minus 100.

3x + 15 = 603x = 60 - 153x = 45x = 45/3Therefore, x = 15.

plot 4y then 3x

x = 10 Minus 6 times 10 = minus 60 Add 3 to minus 60 = minus 57

3(x + 4)(x + 5)

The intercept of -3x + 5y - 2z = 60 are (-20, 0, 0), (0, 12, 0) and (0, 0, -30).

60 because 3x2=6,6x10=60.

The sum is 96.

60 - 20 + 70 = 110

60

the answer is 60

60 + 900 + 7593 + (75739 x 36) - (1200 x 97) + (9462 x 387489) - 7 = 3669039668

Multiply each term of the second expression by each of the terms in the first expression and add them together, collecting like terms together: (x - 6)(3x² + 10x - 1) = x(3x² + 10x - 1) + (-6)(3x² + 10x - 1) = (3x³ + 10x² - x) + (-18x² - 60x + 6) = 3x³ + 10x² - 18x² - x - 60x + 6 = 3x² + (10 - 18)x² + (-1 - 60)x + 6 = 3x² - 8x² - 61x + 6

Around $60 plus or minus

30 plus 30 equals 60 and 60 minus 38 equals 22

It is 18.

420 minus 60 is 360.

It is: x2-16x+60 = (x-6)(x-10) when factored

60

Study guides